Organizational Citizenship Behavior Memediasi Pengaruh Job Satisfaction dan External Work Opportunities Terhadap Turnover Intention - Annisa, Addin Fitri; Assa, Adrie Frans; Tecoalu, Melitina (Universitas Batanghari Jambi, 2024)
Human Resources (HR) are believed as valuable assets for a company in achieving business success and specialized services, especially at PT. Bank Negeri (real company name is hidden). The main purposes of this study are to determine the influence of job satisfaction and external work opportunities on turnover intention, mediated by organizational citizenship behavior (OCB). Another aim of this study is to contribute insights into better HR management for the company. The primary data consisted of questionnaires responses collected from employees at the PT. Bank Negeri Headquarters and secondary data gathered from literature reviews. The research methodology employed includes outer model and inner model analysis, as well as hypothesis testing. Data processing in this study was conducted using Partial Least Square (PLS) with SMART PLS software. The findings of this study resulted that OCB mediates the correlation between job satisfaction and turnover intention but does not mediate the relationship between external work opportunities and turnover intention. These findings offer valuable insights for improved HR management.